All‐trans retinoic acid (ATRA)‐induced TFEB expression is required for myeloid differentiation in acute promyelocytic leukemia (APL). (13th January 2020) - Orfali, Nina; O'Donovan, Tracey R.; Cahill, Mary R.; Benjamin, Dalyia; Nanus, David M.; McKenna, Sharon L.; Gudas, Lorraine J.; Mongan, Nigel P.
Abstract: Objective: In acute promyelocytic leukemia (APL), normal retinoid signaling is disrupted by an abnormal PML‐RARα fusion oncoprotein, leading to a block in cell differentiation. Therapeutic concentrations of all‐ trans ‐retinoic acid (ATRA) can restore retinoid‐induced transcription and promote degradation of the PML‐RARα protein. Autophagy is a catabolic pathway that utilizes lysosomal machinery to degrade intracellular material and facilitate cellular re‐modeling. Recent studies have identified autophagy as an integral component of ATRA‐induced myeloid differentiation. Methods: As the molecular communication between retinoid signaling and the autophagy pathway is not defined, we performed RNA sequencing of NB4 APL cells treated with ATRA and examined autophagy‐related transcripts. Results: ATRA altered the expression of >80 known autophagy‐related transcripts, including the key transcriptional regulator of autophagy and lysosomal biogenesis, TFEB (11.5‐fold increase) . Induction of TFEB and its transcriptional target, sequestosome 1 ( SQSTM1, p62), is reduced in ATRA‐resistant NB4R cells compared to NB4 cells. TFEB knockdown in NB4 cells alters the expression of transcriptional targets of TFEB and reduces CD11b transcript levels in response to ATRA. Conclusions: We show for the first time that TFEB plays an important role in ATRA‐induced autophagy during myeloid differentiation and that autophagy induction potentiates leukemic cell differentiation (Note: this study includes data obtained from NCT00195156, https://clinicaltrials.gov/show/NCT00195156 ).